Healthy Eating: Create Your Plate! - Jennifer Hillan; Linda B. Bobroff (EDIS)
Meal planning can help you control portion sizes and the amount of carbohydrate you eat throughout the day. This is especially important if you have diabetes or if you are at risk for the disease. Let's get started!  This document is FCS8796, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date May 2006.